Posterior Segment Manifestations of Syphilis and Correlation With Serologic Markers of Infection - Rickels, Kaersti L (Ophthalmic surgery, lasers & imaging retina, 2024)
BACKGROUND AND OBJECTIVE: Retrospective analysis correlating serologic titers of ocular syphilis with posterior segment manifestations